D’un centre d’observation à un lieu d’exposition. Histoire(s) et mémoire(s) dans les murs de la justice des enfants - Véronique Blanchard (Criminocorpus)
This article traces the history and objectives of a place marked by the confinement of minors: “Le centre d’expostion Enfants en justice” in Savigny-Sur-Orge. This space is fully in line with the history of judicial heritage, since nearly 25,000 adolescents were placed in this so-called observation center by the juvenile’s court 1945 and 1974. Today, these walls house a museographic space offering visitors a mediation that facilitates the understanding of this place of memory and history. Since the 2000s, the exhibition center has been reflecting on its pedagogy for schools and adults, as well as on the appropriate ways to support the "former inmates" in the restitution of their singular history.